Molecular Identification of Begomovirus Infecting Angled Luffa - Alvina Clara Giovanni; Sedyo Hartono; Sri Sulandari; Susamto Somowiyarjo (Jurnal Perlindungan Tanaman Indonesia, 2020)
Begomovirus was reported as one of the most aggressive and destructive viruses on several commercial crops, including cucurbits in Indonesia. Plants that infected with Begomovirus show the mosaic symptom on the leaves, change in leaf shape, stunts, change in color and shape of fruit. It was recently observed in cultivated angled luffa [Luffa acutangula (L.) Roxb] around Yogyakarta and Central Java. The aim of this research was to identify the virus by using Polymerase chain reaction (PCR). The result of Begomovirus amplification from the total DNA samples amplification using primer Krusty-Homer showed that DNA of Begomovirus from angled luffa was amplified at ~580bp. The DNA sequencing of angled luffa’s leaf isolate GD1 had 97.8% homology with SCLV-China isolate MC1. However, amplification of DNA seed samples using the same primer showed negative result. It was concluded that Begomovirus was not a seed borne virus. This is the first molecular report on the occurence of Begomovirus in angled luffa in Yogyakarta.